Increased miRNA-375 causes oxidative damage but promotes apoptosis resistance and cell migration in the clam Ruditapes philippinarum - Cong, Ming; Li, Zhaoshun; Tian, Wenwen; Yu, Yixian; Che, Yu; Lv, Jiasen (Frontiers in Marine Science, 2025)
MicroRNA is an important regulatory factor at the post-transcriptional level. Previous miRNAomics analysis found that miRNA-375 was steadily upregulated in the clam Ruditapes philippinarum upon ammonia nitrogen exposure. However, we have no knowledge about its regulatory mechanism yet. In this study, the clams were challenged by the injection of miRNA-375 mimics/inhibitor in vivo. Then, a combined approach of qRT-PCR, enzyme assay, and ultrastructure observation was applied to investigate its regulatory effects on the related genes, cellular parameters, and histological structures, respectively. Results showed that increased expression of miRNA-375 interfered with the expression levels of both its target genes and ammonia toxicity-related genes, which would probably lead to oxidative stress, migration of damaged cells, apoptosis resistance, and increased possibility of tumor formation. In addition, miRNA-375 increased MDA content but decreased glutamate content and caused serious structure damage to the clam gills. Thus, increased miRNA-375 probably brings a disastrous fate to the clam R. philippinarum by inducing oxidative damage but promoting apoptosis resistance and cell migration. Overall, this study revealed for the first time the regulatory effects of miRNA-375 in the clams and gave valuable clues to understand the toxicological mechanisms of ammonia nitrogen on the marine bivalve.